Identifikasi Timbulan dan Analisis Pengelolaan Limbah B3 di Pabrik Kertas PT X - Eka Wardhani; Rosmeiliyana Rosmeiliyana (Fakultas Teknik, 2020)
This study aimed to evaluate the management of toxic hazardous materials (THM) in PT. X. The research method uses a comparison technique between the implementation of THM management with the applicable regulations, namely Republic of Indonesia Government Regulation No. 101/2014 concerning management of THM, Minister of Environment Regulation No. 14/2013 concerning the symbol and label of THM, environmental control agency decision No 1/1995 concerning the storage and collection of THM, and environmental control agency decision 2/1995 concerning THM documents. Based on the research PT X has carried out the management of THM in each production unit that produces THM. The types of THM were produced those are ink sludge, WWTP sludge, fly ash, bottom ash, used chemical packaging, ink cans, electronic waste, mercury lamps, toner, filters, and used refrigerants. The characteristics of THM are toxic, corrosive, highly flammable, and infectious. The biggest amount of THM produced in the WWTP sludge. The company has reused WWTP sludge so that it can reduce the amount of sludge produced by 99.83%. The THM management system at PT X follows the work instruction that has been based on applicable regulations. PT X conducts THM management very well.